A SYSTEMATIC LITERATURE REVIEW ON ACADEMIC SUPERVISION AND DIGITAL LEADERSHIP PRACTICES IN CREATING TEACHER’S PERFORMANCE - Hasanudin Hasanudin; Sowiyah Sowiyah; Riswanti Rini; Bujang Rahman; Handoko Handoko (Program Studi PGSD Universitas Flores, 2025)
Principals must be able to empower the teacher’s potential and resources. They must be able to master the development of science and technology. There are various ways that school principals can do to improve teacher performance, one of which is supervision. Educational supervision is very influential in creating the quality of education services, educators, and education staff. This study aims to systematically review and analyze digital leadership and effective academic supervision practices to create teacher technology performance in the education sector. This study uses the PRISMA approach to assist the authors in compiling a quality systematic review and meta-analysis. This study has considered 20 related articles using Scopus and Google Scholar as the main database. The results reveal the importance of academic supervision as well as digital leadership of school principals, especially in the digital era. This systematic literature review also provides several limitations and recommendations for the future.